2011
DOI: 10.1136/oem.2010.057729
|View full text |Cite
|
Sign up to set email alerts
|

A cross-shift study of lung function, exhaled nitric oxide and inflammatory markers in blood in Norwegian cement production workers

Abstract: ObjectivesTo study possible effects of aerosol exposure on lung function, fractional exhaled nitric oxide (FeNO) and inflammatory markers in blood from Norwegian cement production workers across one work shift (0 to 8 h) and again 32 h after the non-exposed baseline registration.Methods95 workers from two cement plants in Norway were included. Assessment of lung function included spirometry and gas diffusion pre- and post-shift (0 and 8 h). FeNO concentrations were measured and blood samples collected at 0, 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…An increase in eNO may have been expected, since this is often seen after exposure to different agents in occupational settings 17. However, a similar response with cross-shift reduction in FEV 1 and eNO was seen in a study in Norwegian cement production workers 18. There might be several different explanations why eNO is reduced.…”
Section: Discussionmentioning
confidence: 75%
“…An increase in eNO may have been expected, since this is often seen after exposure to different agents in occupational settings 17. However, a similar response with cross-shift reduction in FEV 1 and eNO was seen in a study in Norwegian cement production workers 18. There might be several different explanations why eNO is reduced.…”
Section: Discussionmentioning
confidence: 75%
“…14 The lack of difference remained while controlling for height, current dust exposure, duration of employment, working in other dusty industries, RPE use and weight. However, a cross shift study among 95 Norwegian cement production workers reported a small decrease in FENO at 32 h when compared with baseline measurements, but there was no decrease in FENO when the baseline measurements were compared with those at 8 h. 19 The Norwegian study did not have a control group and did not indicate at which time the FENO measurements were performed in relation to exposure, thus, making interpretation of the results difficult. A possible explanation of the results in the current study is that dust exposure among cement production workers may not be associated with eosinophilic inflammation of respiratory airways.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study reported a small across shift decrease in FENO concentration among cement production workers in Norway, but the decrease did not show clear association with dust exposure and lung function changes. 19 Further studies to investigate any associations between dust exposure and FENO concentrations among cement production workers are of importance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, exposure to cement dust was associated with neutrophilic inflammation of the airways and increase in cytokine IL-1β levels,21 but the evidence that cement dust affects lung function in the long term is conflicting. A second study showed small but significant decreases in cross-shift FEV 1 , carbon monoxide diffusion (DLCO) and exhaled nitric oxide (NO) and an increase in leucocytes and fibrinogen counts 22. Some of the cross-sectional studies found no difference in FEV 1 and FVC levels in exposed subjects and unexposed controls23–25 and others reported lower levels of FEV 1 either in exposed compared with unexposed controls26 or increasing exposure-related loss 27 28.…”
Section: Discussionmentioning
confidence: 99%